2014
DOI: 10.1186/2051-5960-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-to-neuron wild-type Tau protein transfer through a trans-synaptic mechanism: relevance to sporadic tauopathies

Abstract: BackgroundIn sporadic Tauopathies, neurofibrillary degeneration (NFD) is characterised by the intraneuronal aggregation of wild-type Tau proteins. In the human brain, the hierarchical pathways of this neurodegeneration have been well established in Alzheimer’s disease (AD) and other sporadic tauopathies such as argyrophilic grain disorder and progressive supranuclear palsy but the molecular and cellular mechanisms supporting this progression are yet not known. These pathways appear to be associated with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
181
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(196 citation statements)
references
References 52 publications
15
181
0
Order By: Relevance
“…The exact mechanism of transmission is not known. Release and trans-synaptic transmission of tau [164,165], tau uptake via exosomes [166][167][168] or nanotubules [169] and free uptake of fibrillar proteins [170,171] have all been suggested as putative mechanisms using cultured neurons. Although astrocyte-to-neuron intercellular transfer mediated by cell-to-cell contact has been postulated for prions [172], no information is available concerning astrocyte-to-neuron transfer in tauopathies.…”
Section: Disease Progression: Seeding and Spreading; Role Of Astrocytesmentioning
confidence: 99%
“…The exact mechanism of transmission is not known. Release and trans-synaptic transmission of tau [164,165], tau uptake via exosomes [166][167][168] or nanotubules [169] and free uptake of fibrillar proteins [170,171] have all been suggested as putative mechanisms using cultured neurons. Although astrocyte-to-neuron intercellular transfer mediated by cell-to-cell contact has been postulated for prions [172], no information is available concerning astrocyte-to-neuron transfer in tauopathies.…”
Section: Disease Progression: Seeding and Spreading; Role Of Astrocytesmentioning
confidence: 99%
“…Tau seeding requires a critical unit of size for activity, as only particular species propagate the aggregated state (16). In vivo studies have described tau protein spreading from local sites to distant regions, presumably via transsynaptic movement (11,12,(17)(18)(19). Finally, our laboratory and another recently demonstrated that tau propagates discrete amyloid conformations through the brains of animals that give rise to unique neuropathologies (18,20).…”
mentioning
confidence: 99%
“…Another important aspect is disease propagation by the secretion and uptake of Tau oligomers that act as seeding templates for Tau misfolding and toxicity (63). In this context, we recently developed a lentivirus-mediated rat model that allowed us to monitor the spreading of Tau pathology from the CA1 region of the hippocampus to other brain areas, including the most distant ones (64,65). We then already used ADx215 as marker to demonstrate that the propagating Tau entity was not phosphorylated at Tyr 18 (65).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we recently developed a lentivirus-mediated rat model that allowed us to monitor the spreading of Tau pathology from the CA1 region of the hippocampus to other brain areas, including the most distant ones (64,65). We then already used ADx215 as marker to demonstrate that the propagating Tau entity was not phosphorylated at Tyr 18 (65). Because ADx215 does not recognize higher order oligomers, the data suggest that Tau monomers or the 130-kDa low order oligomers are propagating Tau entities.…”
Section: Discussionmentioning
confidence: 99%